Positive parenting, adolescent adjustment, and quality of adolescent diet in nine countries. Issue 8 (6th September 2022) - Zietz, Susannah; Cheng, Emily; Lansford, Jennifer E.; Deater‐Deckard, Kirby; Di Giunta, Laura; Dodge, Kenneth A.; Gurdal, Sevtap; Liu, Qin; Long, Qian; Oburu, Paul; Pastorelli, Concetta; Skinner, Ann T.; et al.
Abstract: Introduction: We sought to understand the relation between positive parenting and adolescent diet, whether adolescents' internalizing and externalizing behaviors mediate relations between positive parenting and adolescent diet, and whether the same associations hold for both boys and girls and across cultural groups. Methods: Adolescents ( N = 1334) in 12 cultural groups in nine countries were followed longitudinally from age 12 to 15. We estimated two sets of multiple group structural equation models, one by gender and one by cultural group. Results: Modeling by gender, our findings suggest a direct effect of positive parenting at age 12 on a higher quality diet at age 15 for males ( β = .140; 95% CI: 0.057, 0.229), but an indirect effect of positive parenting at age 12 on a higher quality diet at age 15 by decreasing externalizing behaviors at age 14 for females ( β = .011; 95% CI: 0.002, 0.029). Modeling by cultural group, we found no significant direct effect of positive parenting at age 12 on the quality of adolescent diet at age 15. There was a significant negative effect of positive parenting at age 12 on internalizing ( β = −.065; 95% CI: −0.119, −0.009) and externalizing at age 14 ( β = −.033; 95% CI: −0.086, −0.018). Conclusions: We founder gender differences in the relations among positive parenting, adolescents' externalizing and internalizing behaviors, and adolescent diet. Our findings indicate that quality of parenting is important not only in promoting adolescent mental health but potentially also in promoting the quality of adolescents' diet.